Real-world analysis of community colorectal neoplasia screening based on stool DNA methylation detection - Fu, Ming-sheng; Pan, Shu-xian; Cai, Xun-quan; Cao, Ya-wen; Jin, Li-yuan; Pan, Qin-cong (Frontiers in Oncology, 2025)
This study aimed to assess the effectiveness of stool DNA methylation detection (sDNAMD) in improving colorectal neoplasia (CN) detection rates and colonoscopy compliance in a real-world community setting. Between July 1, 2023, and June 30, 2024, residents aged 50–75 from Maqiao Town, Minhang District, Shanghai, were invited to participate in a CN screening program. Participants were randomly assigned to one of three groups: high-risk questionnaire + fecal occult blood test (HRFO), high-risk questionnaire + FOBT + sDNAMD (HRFOsD), or sDNAMD only (sDNA). Colonoscopy was performed based on initial screening results, and the number of individuals undergoing colonoscopy, along with results, were recorded to calculate compliance and CN detection rates. The HRFOsD group exhibited a significantly higher colonoscopy compliance rate (93.7%) compared to the HRFO (32.6%) and sDNA (73.5%) groups (P<0.0001). Residents with negative FOBT, negative sDNA results, or those who did not undergo sDNA testing did not undergo colonoscopy. In the HRFOsD group, the CN detection rate was higher in females compared to males. Compared to the HR and FOBT+ group, the CN detection rate was significantly higher in the LR and FOBT+ and sDNA+ group. Adding sDNAMD to the high-risk questionnaire and FOBT screening led to a notable increase in both colonoscopy compliance and CN detection rates. The conclusion is that adding stool DNA methylation detection to the community FOBT screening program can significantly improve colonoscopy compliance and colorectal neoplasia detection rates among community residents.